Karakteristik Tanaman Jeruk (Citrus sp.) Di Plot Biospropeksi Spesies Jeruk Terpilih - Arezsya, Muhammad Bagus; Risnawati; Shafie, Muhammad (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2025)
Citrus (Citrus sp.) is a strategic horticultural commodity with not only high economic value but also significant biodiversity that supports both conservation and breeding efforts. This study is motivated by the need to identify local citrus varieties that are adaptive to environmental changes and possess promising genetic potential. The objective of this research is to describe the vegetative and generative morphological characteristics of citrus plants within a biosprospection plot of selected species. A descriptive-explorative approach was employed through direct field observation of five local citrus varieties: limau nipis, limau kasturi, limau muncung, limau pagar, and limau mata kerbau. Morphological observations covered characteristics of leaves, stems, and fruits, documented through visual notes and photographic records. The results revealed significant phenotypic variation among the varieties, particularly in canopy shape, leaf morphology and color, presence of stem thorns, as well as fruit size, color, and taste. For instance, limau pagar exhibited thorny stems and deeply wrinkled fruit, while limau mata kerbau bore large, sweet, and refreshing fruits with broad leaves as a form of ecological adaptation. These findings highlight the role of biosprospection plots as natural laboratories for conserving genetic resources and selecting adaptive varieties. The study’s outcomes are expected to contribute to germplasm preservation and the sustainable development of local-species-based horticulture. Citrus (Citrus sp.) is a strategic horticultural commodity with not only high economic value but also significant biodiversity that supports both conservation and breeding efforts. This study is motivated by the need to identify local citrus varieties that are adaptive to environmental changes and possess promising genetic potential. The objective of this research is to describe the vegetative and generative morphological characteristics of citrus plants within a biosprospection plot of selected species. A descriptive-explorative approach was employed through direct field observation of five local citrus varieties: limau nipis, limau kasturi, limau muncung, limau pagar, and limau mata kerbau. Morphological observations covered characteristics of leaves, stems, and fruits, documented through visual notes and photographic records. The results revealed significant phenotypic variation among the varieties, particularly in canopy shape, leaf morphology and color, presence of stem thorns, as well as fruit size, color, and taste. For instance, limau pagar exhibited thorny stems and deeply wrinkled fruit, while limau mata kerbau bore large, sweet, and refreshing fruits with broad leaves as a form of ecological adaptation. These findings highlight the role of biosprospection plots as natural laboratories for conserving genetic resources and selecting adaptive varieties. The study’s outcomes are expected to contribute to germplasm preservation and the sustainable development of local-species-based horticulture.